Miscarriage. Issue 1 (January 2018) - N/A,
Abstract : Compassionate, helpful, sensitive nursing care to women experiencing early pregnancy loss is the goal of providing the content of the four articles in this special topics series to MCN readers. Each article has a specific focus on an important aspect of care for women having a miscarriage.